Sustainable Grocery Shopping Habits among Gen Z Consumers in the Czech Republic - De Beuckelaerová, Karolien; Volfová, Jitka, 1982-; Matysová, Kamila; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
Given the increasing urgency of addressing environmental issues and the significant contribution of the food industry to climate change, shifting consumers’ food consumption habits has become critical to securing a future for the next generations. Consumers therefore play a crucial role in reducing the burden on the environment through their food choices. However, while public interest in sustainability and environmental protection is increasing and attitudes are predominantly positive, actual consumption patterns often fail to reflect these attitudes. This discrepancy, known as the attitude-behaviour or intention-behaviour gap, is particularly evident among members of Generation Z. Although they express strong pro-sustainability values, they frequently opt for less sustainable options. The study is based on Ajzen’s Theory of Planned Behaviour (1991) and applies a qualitative research design to gain a deeper understanding of the purchasing behaviour of Generation Z consumers in the Czech Republic. The aim is to examine how various factors influence consumer decisions and contribute to the persistence of the attitude-behaviour gap in sustainable food purchasing within supermarket contexts. By linking individual barriers and motivational drivers with the situational factors encountered in supermarkets, the thesis provides insights into how these dynamics interact at the point of purchase. The findings reveal that in-store dynamics (the interaction of individual and situational factors) significantly shape final purchasing decisions. The shopping environment has the potential to mitigate barriers and leverage motivational drivers, helping to make sustainable choices not only accessible but also intuitive. Based on these insights, practical recommendations are proposed to support retailers in adjusting the shopping environment in a way that encourages sustainable decision-making among Generation Z consumers.
Vedoucí práce: Jitka Volfová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses